MAKNA DAKWAH LIRIK LAGU PINTU TAUBAT: PERSPEKTIF SEMIOTIK - Andri (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2023)
The purpose of this study is to unravel the meaning of latent in da'wah lyrics of Pintu Taubat song sung by the band Zivilia. This research is included in a critical paradigm, using a semiotic blade of Sander Pierce analysis. The conclusion of the research is the lyrics of the song Pintu Taubat has three apsek meaning that is aqidah, syariah, and worship. The meaning of the aspect of aqidah includes faith in Allah SWT and all its properties. The meaning of the moral aspect of the consciousness of error and sin, consciousness as a weak creature, a deep remorse of the sins ever committed, consciousness as a weak and despicable creature, consciousness will need for God's forgiveness and fear and anxiety if the remaining age is not enough to remove the sins and mistakes ever done. Meaning in the aspect of worship includes, prostrating as a sign of asking God's forgiveness, praying that sin is forgiven and istighfar in an attempt to get the forgiveness.